TEORI PERUSAHAAN (THEORY OF FIRM): KAJIAN TEORI EKONOMI MIKRO DALAM PERSPEKTIF EKONOMI SYARIAH - Ginting, Sri Wahyuni Br (Jurnal AKMAMI (Akuntansi Manajemen Ekonomi), 2025)
The theory of the firm in this study discusses how to apply microeconomic theory and its application to Islamic economics, in addition, this theory of the firm also discusses how companies can operate, compete and survive in various economic conditions, when companies get various challenges in determining strategies, deciding on production scales, determining prices and choosing the right production methods to be used efficiently. In addition, there is an influence of zakat on this company theory. This study uses a qualitative method, namely by using a literature review or also called a literature review. From the results of this study, it is hoped that the company that grows in the midst of community life can be used in the process of mutual benefit, and the application of this microeconomics can not only be applied in conventional economics, but in Islamic economics it can also be applied well.